Last one to know ebook - Freethy, Barbara (Fog City Publishing, 2022)
Barbara Freethy delivers riveting, plot-twisting suspense and a deeply emotional story. Every book is a thrilling ride." USA Today Bestselling Author Rachel Grant I was working at my sister's clothing boutique in Carmel when I got the call. The hospital told me that my mother had been shot and was in critical condition. This could be my last chance to see her, and I needed to go to San Francisco immediately. I was stunned. Not just because of the horrific news, but also because my mother had died in a storm twenty years ago... To find out the truth, I'll have to dive into the life of the woman in the hospital bed, into her past and mine. But as I get closer to the truth, the target moves from her to me...and suddenly her life isn't the only one on the line. From #1 New York Times Bestselling Author Barbara Freethy comes a tangled, twisty tale of secrets and lies in a thrilling, page-turning standalone domestic thriller that will keep you up all night! What the readers are saying about Barbara's suspense novels... "Barbara Freethy's suspense novels are explosively good!" — New York Times Bestselling Author Toni Anderson "Powerful and absorbing...sheer hold-your-breath suspense." — NYT Bestselling Author Karen Robards on Don't Say A Word "A heart-stopping thriller that goes to the head. Freethy plays the ultimate mind game with chilling results. The twists keep coming. The danger is haunting, and the emotions are riveting. Step inside a nightmare that will steal your breath and touch your heart." Isha – BookBub on ALL THE PRETTY PEOPLE "A fabulous, page-turning combination of romance and intrigue." Fans of Nora Roberts will love this book." — NYT Bestselling Author Kristin Hannah on Golden Lies "WOW! ALL THE PRETTY PEOPLE is another wonderful page turner, suspense filled mystery with more twists and turns than a roller coaster." Cheryl – Goodreads "All the Pretty People is a five stars emotional thriller. Barbara Freethy knows how to snag reader's attention immediately and never let it disengage until the last period. So many secrets and lies will be revealed in a tight plot that will keep one guessing." Jane – Goodreads "PERILOUS TRUST is a non-stop thriller that seamlessly melds jaw-dropping suspense with sizzling romance, and I was riveted from the first page to the last...Readers will be breathless in anticipation as this fast-paced and enthralling love story evolves and goes in unforeseeable directions." — USA Today HEA Blog